Legal support for the development of sustainable and secure information and telecommunications infrastructure - Andrey L. Belousov (RUDN Journal of Law, 2023)
The relevance of the work is due to the need to adapt regulatory mechanisms to the actively developing digitalization processes. On the other hand, in the context of growing cyber threats and increasing dependence of public relations on information and telecommunications technologies, the directions for the development of legislation that ensure stability and security of the relevant infrastructure are subject to a certain rethinking in the legal aspect. The subject of the study is the legal support for the development of a sustainable and secure information and telecommunications infrastructure. The purpose of the work is to identify key areas for improving legal regulation in the field of functioning and development of sustainable and secure information and telecommunications infrastructure. The study applies methods of analysis, synthesis and comparison, as well as literal and systematic interpretation of the norms of the current legislation in the field of functioning and developing sustainable and secure information and telecommunications infrastructure. Finally, conclusions are formulated regarding the need for the development of legal regulation in this area. The research outlines the specific directions for changing the legal field, which ensure the sustainable development of information and telecommunications infrastructure in the Russian Federation.